Biodiversity Journal 2018
DOI: 10.31396/biodiv.jour.2018.9.3.283.302
|View full text |Cite
|
Sign up to set email alerts
|

Marine molluscs from Cape Milazzo (Sicily, Italy): a baseline

Abstract: An original data set of 556 benthic mollusc taxa, as a first account of Cape Milazzo local biodiversity, is provided. Qualitative differences between more or less anthropized areas have been put in evidence, and species distribution according to the main habitat typologies has been detailed. The highest biodiversity was found in the northern sites, corresponding to the Zone A of the established marine protected area. Most mollusc species under the European Economic Community (EEC) and National protection, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This introduced Red Sea species, widely spreading in Mediterranean and firstly reported by [47] for the Strait of Messina area (between the Tyrrhenian and Ionian Seas), was never found during our investigation. Similarly, H. orteai Talavera, Murillo and Templado, 1987, first reported in Faro Lake by [21], was not detected in our collected samples, although it occurs elsewhere in the Strait (as demonstrated by the specimen with voucher RM3_2222). By contrast, the occurrence of H. hydatis (Linnaeus, 1758) and H. navicula (da Costa, 1778), both cited by [22] as characterizing Faro Lake and Ganzirri Lake mollusk fauna, is confirmed here.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This introduced Red Sea species, widely spreading in Mediterranean and firstly reported by [47] for the Strait of Messina area (between the Tyrrhenian and Ionian Seas), was never found during our investigation. Similarly, H. orteai Talavera, Murillo and Templado, 1987, first reported in Faro Lake by [21], was not detected in our collected samples, although it occurs elsewhere in the Strait (as demonstrated by the specimen with voucher RM3_2222). By contrast, the occurrence of H. hydatis (Linnaeus, 1758) and H. navicula (da Costa, 1778), both cited by [22] as characterizing Faro Lake and Ganzirri Lake mollusk fauna, is confirmed here.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, in proportion to its small extent, the lake can be considered a hotspot for heterobranchs, as testified by the 47 species reported by [20], which includes four morphologically identified species of the genus Haminoea. Prior to their study, only two previous [21] and dated [22] checklists had reported Haminoea species from Faro Lake; however, none of them included a molecular identification of the species recorded.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the brackish basins are concerned, the literature containing information about Lake Ganzirri's biodiversity is limited [66]. This is different to the literature concerning the highly biodiverse Lake Faro, for which some faunal and floristic lists have been published [67,68], as well as data on different biological items (e.g., [69]). Only in the last decade a revised list of the macroalgal flora and their molecular bases has been underway [70][71][72][73].…”
Section: Study Areamentioning
confidence: 99%